2018
DOI: 10.1038/s41598-018-28784-1
|View full text |Cite
|
Sign up to set email alerts
|

Twinning-induced strain hardening in dual-phase FeCoCrNiAl0.5 at room and cryogenic temperature

Abstract: A face-centered-cubic (fcc) oriented FeCoCrNiAl0.5 dual-phase high entropy alloy (HEA) was plastically strained in uniaxial compression at 77K and 293K and the underlying deformation mechanisms were studied. The undeformed microstructure consists of a body-centered-cubic (bcc)/B2 interdendritic network and precipitates embedded in 〈001〉-oriented fcc dendrites. In contrast to other dual-phase HEAs, at both deformation temperatures a steep rise in the stress-strain curves occurs above 23% total axial strain. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 47 publications
(70 reference statements)
3
12
0
Order By: Relevance
“…In order to discern the role of the constituent two phases and the salient deformation mechanisms, the DP-HEA was investigated using several nanoscale techniques, including in situ straining tests and quantitative in situ compression tests in the TEM, state-of-the-art spherical aberration-corrected scanning transmission electron microscopy (STEM) and energy-dispersive x-ray spectroscopy (EDS) with atomic resolution. Although deformation-induced phase transformations are known to occur in DP-HEAs [12][13][14][15][16] , our current in situ TEM studies demonstrate that the phase transformation from fcc to hcp is based on the formation of three-dimensional (3D) stackingfault networks comprising multiple stacking faults (SFs) and sessile Lomer-Cottrell locks, which we believe are promoted by intrinsic chemical variation in HEAs. We further employ nanoscale compression pillar testing to establish the mechanisms underlying how this continuous fcc → hcp phase transformation plays a dominant role in generating the significant strain hardening in this HEA.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…In order to discern the role of the constituent two phases and the salient deformation mechanisms, the DP-HEA was investigated using several nanoscale techniques, including in situ straining tests and quantitative in situ compression tests in the TEM, state-of-the-art spherical aberration-corrected scanning transmission electron microscopy (STEM) and energy-dispersive x-ray spectroscopy (EDS) with atomic resolution. Although deformation-induced phase transformations are known to occur in DP-HEAs [12][13][14][15][16] , our current in situ TEM studies demonstrate that the phase transformation from fcc to hcp is based on the formation of three-dimensional (3D) stackingfault networks comprising multiple stacking faults (SFs) and sessile Lomer-Cottrell locks, which we believe are promoted by intrinsic chemical variation in HEAs. We further employ nanoscale compression pillar testing to establish the mechanisms underlying how this continuous fcc → hcp phase transformation plays a dominant role in generating the significant strain hardening in this HEA.…”
Section: Resultsmentioning
confidence: 71%
“…For example, Li et al 12 reported a dual-phase high-entropy alloy (DP-HEA) that displays higher tensile yield strength and ductility than many single-phase HEAs (including the Cantor alloy). Subsequently, other DP-HEAs have been developed with excellent mechanical properties that exceed most traditional dual-phase alloys [13][14][15][16] . Different from many other dual-phase systems 17,18 , the fcc phase in these DP-HEAs can easily transform to the hcp phase through the glide of partial dislocations 16,[19][20][21] ; consequently, the volume fraction of the two phases can progressively change during plastic deformation 22 , resulting in a steady hardening effect with increasing strain under high stress.…”
mentioning
confidence: 99%
“…In the last two decades, research on high entropy alloys (HEAs) aimed at finding alloys that would allow obtaining single-phase equiatomic HEAs exhibiting face-centered-cubic (FCC), body-centered-cubic (BCC), and hexagonal-close-packed (HCP) structures while eliminating secondary (and tertiary) phases (Kozak et al, 2015;Steurer, 2020). However, in recent years a paradigm shift has taken place that puts the focus on dual-phase (or multi-phase) HEAs and intentionally takes advantage of their heterophase nature to achieve superior mechanical properties (Bönisch et al, 2018). Furthermore, increasing attention is given to medium entropy alloys with less than five elements, not at least with the aim of avoiding expensive and resourcecritical elements like Cobalt (Tkaczyk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The alloy system Al-(Co)-Cr-Fe-Ni also offers means to exploit some features of spinodal decomposition (Langer, 1971) for microstructure tailoring. Novel dual phase materials have been reported in the system Al-(Co)-Cr-Fe-Ni (Dong et al, 2016;Abuzaid and Sehitoglu, 2018;Bönisch et al, 2018;Gwalani et al, 2019;Li Z. et al, 2020). Unique so far are vermicular duplex microstructures (Dong et al, 2016; composed of an ultrafine vermicular FCC phase intertwined with a spinodally decomposed BCC in nearly equal volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetics way of tailoring phases is significantly important for HEAs to obtain outstanding integrated performance. Al x CoCrFeNi (0 ≤ x ≤1) HEAs are one of the most commonly investigated alloys that owns very good properties and easily to be tunable by changing the Al content, heat treatment and forging [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%